Depressive and Anxious Temperaments as Predictors of Late Onset Bipolar Disorder? Preliminary Results of a “Real World” Exploratory Study - Orsolini, Laura; Menculini, Giulia; Tempia Valenta, Silvia; Fiorani, Michele; Rocchetti, David; Salvi, Virginio; Tortorella, Alfonso; Volpe, Umberto (Frontiers in Psychiatry, 2022)
Introduction: Bipolar disorder (BD) onset typically occurs between 15 to 30 years, being diagnosed under the age of 50 in 90% of cases, named ‘non-late onset BD’ (non-LOBD). However, clinical observation of late-onset BD (LOBD) raised some concern regarding a differential psychopathological pattern, outcomes and treatment, including a specific affective temperament vulnerability. Therefore, an exploratory study in the ‘real world’ was carried out by investigating psychopathological and temperamental features of a psychogeriatric cohort of LOBD and non-LOBD subjects. Methods: A total of 180 patients affected with BD-I, BD-II, and Cyclothymic Disorder were screened in a Mood Disorder Outpatient Service, during the timeframe January 2019-August 2021. Out of 78 enrolled outpatients, 66 (33 non-LOBD, 33 LOBD) were recruited, by the retrospective collection of sociodemographic, cognitive, psychopathological and clinical assessment, including the short-version of the Temperament Evaluation of Memphis, Pisa, and San Diego (TEMPS-M). Results: LOBD is significantly associated with higher rates of BD-II diagnosis (χ2=27.692, p<0.001), depressive episodes (p=0.025), mixed states (p=0.009), predominant depressive and anxious affective temperaments (p<0.001). Non-LOBD is significantly associated with higher endocrinological (χ2=6.988, p=0.008) and metabolic comorbidity (χ2=5.987, p=0.014), a diagnosis of BD-I, manic episodes, and predominant hyperthymic affective temperaments (p=0.001). GDS (p<0.001) and MSRS (p=0.005) scores were significantly higher in LOBD. Conclusion: Further longitudinal studies with larger sample sizes and a control group are needed to determine whether LOBD may represent a distinct psychopathological entity from non-LOBD and evaluate differences (if any) in terms of prognosis and treatment between non-LOBD and LOBD.